Gli studi di “cost of illness” in Italia: una review della letteratura - Bracco, Andrea (Farmeconomia. Health economics and therapeutic pathways, 2001)
The cost of illness studies (COI) attempt to measure the economic burden of a specific pathology. A standardised protocol identifies three components in the COI studies: direct costs, indirect costs and intangible costs.Aim of this paper is to review the status of COI studies in Italy, searching Medline, the New York City University database, the IES database and the S.A.V.E. database according to these keywords: “Cost of Illness Italy” and “Italian Cost Analysis”. The research detected 24 studies, but only 17 complete studies has been included in this review. For being reliable, the study had to present detailed informations about: - kind of approach (bottom-up or top-down); - annual average cost for single patient and single pathology; - pathology incidence or prevalence; - methods for calculating direct and indirect costs. The studies in this review examine the following pathologies: Alzheimer’s disease, diabetic foot, schizophrenia, type 2 diabetes, epilepsy, measles, dyspepsia, hypertension, asthma, varicella, osteoporosis, benign prostatic hyperplasia, urinary incontinence, hepatitis A and hepatitis B.